THERAPEUTIC COMMUNICATION - Dwi Andriani, Astri; Saniah, Lia (Universitas Efarina, 2022)
The purpose of this research is to know descriptive knowledge about therapeutic communication skills. To get this result, this research uses a descriptive qualitative approach where by collecting data that is supplied by sentences in it. Literature Review Steps include: Systematic Identification, Document Analysis containing information about the problem of problems. In this study, data collection methods used by researchers are documentation methods, data on data about matters or variables in books, newspapers, journals, and so on. Books, literature, and notes about the problems to be discussed. The techniques used are content analysis or content review. The results of this study are: Communication is an important factor in medical professional careers and service success in the world of health. Medical professionals, such as doctors, nurses, midwives, pharmacists, and others need communication to support their work success. The results of the study revealed that good communication between doctors and patients at the hospital indicated progress or improvement in the patient's physical and emotional health, as well as better control of various chronic diseases. Communication that is planned consciously, aims and activities are centered on patient recovery is referred to as therapeutic communication. Therapeutic communication is very important and useful for patients, because good communication can provide an understanding of patient behavior and help patients overcome the problems they face.